The Military Policy of the Rousseff Government: Reflections on the Conduct of the Armed Forces in the UPP and the MINUSTAH - Mathias, Suzeley Kalil; Campos, Bruce Scheidl; Santos, Leandro Fernandes Sampaio (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2016)
This article attempts to analyze how operations to guarantee order are represented in the military policy of the government of Dilma Rouseff and how these missions are related to the creation of the Police Pacification Units (UPP) in Brazil. The UPPs are a key attribute of public security of the government carioca in Brazil and by extension the Brazilian state. The question is whether the missions of the Brazilian armed forces reinforce or are contrary to the foreign policy of the Rouseff government? To parse this issue, this article is divided into three parts. This first section analyzes the legal framework that governs the Brazilian armed forces as well as the country’s contemporary military policy. This establishes the theoretical basis for the issues analyzed in this article. In the next section we describe the UPPs and why they were created, focusing on the case of Rio de Janeiro. Finally we examine several aspects of the participation of the Brazilian armed forces in the United Nations Mission for the Stabilization of Haiti (MINUSTAH).